Evaluasi Kinerja Aplikasi Penelusuran Online Cerah Informasi Pustaka (CIP) Perpustakaan Universitas Tridinanti Palembang Berdasarkan Persepsi Pustakwan - Rusmiatiningsih, Rusmiatiningsih; Solehati, Indah; Sagiman, Sagiman; Marleni, Marleni (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2024)
This study aims to evaluate the performance of the online search service system on the Cerah Informasi Pustaka application at the Tridinanti University Library Palembang in terms of librarian perceptions. The purpose of this research is to find out and ensure that the Cerah Informasi Pustaka application functions optimally in supporting library operations and meeting the needs of its users. this research uses a qualitative approach research methodology with data collection techniques through interviews, observation and documentation to an informant, namely the librarian of the Tridinanti University Library Palembang. The evaluation model used is the PIECES evaluation model by making a questionnaire based on 6 variables, namely Performance, Information, Economy, Control, Efficiency and Service and each variable is made into indicators. The results showed that the performance of the Bright Online Search Application of Information Library of Tridinanti University Palembang Library in terms of the librarian's point of view showed that the system was good in carrying out its functions